Catalytic enolate arylation with 3-bromoindoles allows the formation of β-carbolines. - Alves Esteves, C; Smith, P; Donohoe, T (American Chemical Society, 2017)
Synthesis of substituted β-carbolines was accomplished by utilizing the catalytic enolate arylation reaction of ketones in conjunction with several 3-bromoindole derivatives. Quenching of the arylation reaction in situ with an electrophile allowed ready incorporation of functionality at the carboline C-4 position in an efficient one-pot protocol.